Sources of variation in plant responses to belowground insect herbivory: a meta-analysis - Zvereva EL; Kozlov MV (SPRINGER, 2022)
Growing interest in belowground herbivory and the remarkable diversity of the accumulated information on this topic inspired us to quantitatively explore the variation in the outcomes of individual studies. We conducted a meta-analysis of 85 experimental studies reporting the effects of root-feeding insect herbivores (36 species) on plants (75 species). On average, belowground herbivory led to a 36.3% loss of root biomass, which was accompanied by a reduction in aboveground growth (-16.3%), photosynthesis (-11.7%) and reproduction (-15.5%). The effects of root herbivory on aboveground plant characteristics were significant in agricultural and biological control studies, but not in studies of natural systems. Experiments conducted in controlled environments yielded larger effects on plants than field experiments, and infestation experiments resulted in more severe effects than removal studies employing natural levels of herbivory. Simulated root herbivory led to greater aboveground growth reductions than similar root loss imposed by insect feeding. External root chewers caused stronger detrimental effects than sap feeders or root borers; specialist herbivores imposed milder adverse effects on plants than generalists. Woody plants suffered from root herbivory more than herbaceous plants, although root loss was similar in these two groups. Evergreen woody plants responded to root herbivory more strongly than deciduous woody plants, and grasses suffered from root herbivory more than herbs. Environmental factors such as drought, poor nutrient supply, among-plant competition, and aboveground herbivory increased the adverse effects of root damage on plants in an additive manner. In general, plant tolerance to root herbivores is lower than tolerance to defoliating aboveground herbivores.